Pengaruh Gaya Kepemimpinan Dan Beban Kerja Terhadap Produktivitas Kerja Karyawan Pada PT Dinasti Kreatif Indonesia Tangerang Selatan - Ahmad Maulana Yusup Badar; Muhammad Gandung (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstrak. The purpose of this study is to determine the effect of leadership style and workload on employee productivity at PT Dinasti Kreatif Indonesia, both partially and simultaneously. The research uses a quantitative approach with a causal method. The sample consists of 80 respondents who are employees of PT Dinasti Kreatif Indonesia, and data were collected through questionnaires. Data analysis was carried out using multiple linear regression with the help of SPSS version 26. The results show that: (1) leadership style has a significant effect on work productivity with a t-value of 4.419 > t-table 1.664 and a significance value of 0.000 < 0.05, contributing 47.8%; (2) workload has a significant effect on work productivity with a t-value of 7.588 > t-table 1.664 and a significance value of 0.000 < 0.05, contributing 62.5%; and (3) simultaneously, leadership style and workload have a significant effect on work productivity with an F-value of 90.377 > F-table 3.11 and a significance value of 0.000 < 0.05. The coefficient of determination (R Square) of 0.701 indicates that both variables contribute 70.1% to employee productivity, while the remaining 29.9% is influenced by other factors outside this study. Therefore, the better the implementation of leadership style and the more optimal workload management, the higher the employee work productivity Keywords: leadership style, workload, work productivity, PT Dinasti Kreatif Indonesia.